Malaysians' Preferences and Concerns Regarding Seeking Information About Illegal Drugs - Qiu Ting Chie; Cai Lian Tam; Gregory Bonn (Frontiers Media S.A., 2018)
A brief survey asked Malaysians if they had searched for information about illegal drugs and their thoughts about the information available. Two hundred and eighty participants from four states: Selangor, Penang, Malacca, and Johor filled out a paper-and-pencil survey including both multiple choice and open-ended written questions. Quantitative analyses of closed-ended, and thematic analyses of open-ended data indicated the following: Half of participants had, at some point, actively searched for information about drug use; 28% reported searching at least once per month. Participants generally (79%) preferred to obtain information online, but 62% also reported sharing and obtaining information about drugs in face-to-face interactions with friends and others. Concerns regarding the reliability of information, such as the presence of conflicting or contradictory messages from multiple sources, was a common theme in open ended responses. Of those who searched for information, about 70% reported desiring more detailed information about different drugs, in particular about their various side effects and risks. It is suggested that drug information campaigns, particularly those aimed at university students, might better focus on providing accurate, detailed information about the risks and other issues involved in various types of drug use, rather than one-size-fits-all messages. Given the varied and confusing nature of information already available, overly simplistic anti-drug messages may be ineffective, if not counterproductive.